A Literature Review of the Relation Between Iron Deficiency Anaemia, Physical Activity and Cognitive Function in Adolescent Girl - Yunanci, Sri; Risma, Risma; Masrif, Masrif; Mulianingsih, Misroh (Scripta Medica, 2023)
Women, especially those young and/or pregnant, are at high risk of experiencing an iron deficiency. Low iron stores in the body can affect cognitive function and physical activity in adolescents, but the results of epidemiological studies about the effect of iron deficiency on cognitive function decline and physical activity in adolescents are not consistent. Therefore, it is necessary to review the literature on the relationship between iron deficiency, cognitive function and physical activity in women and girls. This study is an article review using sources from Google Scholar, PubMed and ProQuest database searches from 2014 to 2021. The keywords used are iron deficiency OR anaemia AND adolescent girls OR young women AND activity AND cognitive. By using review criteria, sources were limited to those in English that used a sample of adolescents or young women. In the initial search stage, 63 reviews were obtained and based on the predetermined criteria, 12 reviews were selected to be analysed. Eleven studies examined the relationship between iron deficiency and cognitive decline, there was one study that showed a non-significant relationship between the two; ten studies showed a significant effect of iron deficiency on cognitive decline in the domains of attention tasks, memory tasks and executive function. Three studies showed their effect on decline in adolescents by using different measuring tools. Lack of iron in the body caused a decrease in cognitive function, especially in the domain attention tasks, memory task domains and executive functions domains. In addition, iron deficiency can cause a decrease in physical activity in adolescents due to the low supply of oxygen to the blood and tissues. Therefore, it is necessary to research nutrition intervention programs to improve iron anaemia status in adolescent girls and prevent a decline in cognitive function and physical activity as a result of the impact of iron deficiency.
Keywords: Iron deficiency; Adolescence; Activity; Cognitive